Analisis Kepuasan Kerja Karyawan untuk Meningkatkan Daya Saing pada Amarterra Villas Resort Bali Nusa Dua, Autograph Collection - Kadek Narindra Asri Putria Daniswara; Ida Bagus Sanjaya; Made Ayu Jayanti Prita Utami (Lembaga Pengembangan Kinerja Dosen, 2026)
The increasingly competitive hospitality industry requires companies to strengthen their competitiveness through effective human resource management. One of the key factors influencing organizational competitiveness is employee job satisfaction. Amarterra Villas Resort Bali Nusa Dua , Autograph Collection faces challenges in maintaining employee job satisfaction, as indicated by fluctuating employee turnover rates and gaps between employees' expectations and their perceived working conditions. This study aims to determine the level of employee job satisfaction, map job satisfaction attributes using the Importance Performance Analysis (IPA) method, and formulate improvement strategies to enhance employee job satisfaction in order to strengthen the company's competitiveness. This research employed a descriptive quantitative approach involving 45 employees selected using the Slovin formula. Data were collected through observation, interviews, documentation, and questionnaires, and analyzed using validity testing, reliability testing, conformity level analysis, and the Importance Performance Analysis (IPA) method. The results indicate that the average conformity level of employee job satisfaction reached 99.46%, suggesting that employees' expectations have generally been fulfilled. However, several attributes remain priorities for improvement (Action), particularly those related to salary, promotion opportunities, certain aspects of coworker relationships, and the relationship between employees and supervisors. Meanwhile, attributes associated with supervisor recognition, the work itself, and several coworker-related aspects fall into the Hold category and should therefore be maintained. The findings are expected to provide managerial recommendations for improving employee job satisfaction as a strategic effort to enhance the competitiveness of Amarterra Villas Resort Bali Nusa Dua, Autograph Collection.